2016
DOI: 10.1155/2016/8013175
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Concentrations of Steroids in Bulls under Anabolic Treatment by Revalor-XS® Implant

Abstract: Despite the European ban of using anabolics in food-producing animals, growth promoters might still be illegally used in the European Union. To control the food chain and guarantee consumers' health, there is a need of highly sensitive analytical methods for the identification of marker residues of such treatments. In the present study, a group of bulls (n = 16) received trenbolone acetate (200 mg) and estradiol (40 mg) by a commercial ear implant during a time range of 71 days, and a second group (n = 16) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…The APCI and ESI sources were evaluated and compared for ionization efficiency and analytical signal stability. The ESI source provided more intense and stable analytical signals than APCI for most of the analytes (Figure ), which is in agreement with the literature, in which the former source is preferably used for veterinary drugs with lower polarities. , , …”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…The APCI and ESI sources were evaluated and compared for ionization efficiency and analytical signal stability. The ESI source provided more intense and stable analytical signals than APCI for most of the analytes (Figure ), which is in agreement with the literature, in which the former source is preferably used for veterinary drugs with lower polarities. , , …”
Section: Resultssupporting
confidence: 88%
“…In this way, it could be observed that the optimized method is simpler than other works reported in the literature. For instance, it did not require the use of the SPE techniques, , ,, which are related to time-consuming experiments that demand great amounts of organic solvents for the conditioning and washing steps. In addition, the developed sample extraction protocol did not use any chemical derivatization reaction, which usually leads to more expensive and longer procedures. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The urinary concentration of drug residues in treated and control animals has been measured and previously published to prove the efficacy of drug administration, distribution, and excretion . Anabolic compounds were monitored in urine throughout the experiments and/or in target organs, attesting for complete urinary excretion when few days of drug administration suspension are applied (Table S3, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Illegal use of steroid GP at a high dose, that is, 7mg/kg [ 12 ] and their residues in food products may negatively impact children’s mental and physical growth and women’s fertility, cause cancer, and damage vital organs such as brain, liver, kidney, and heart [ 13 ]. Due to these health concerns, some of the steroid GPs were banned from using in food-producing animals by the European Union (EU) [ 14 , 15 ]. To protect the consumer health from any potential risks, the EU approved the use of DEX in livestock for therapeutic purposes only and set appropriate maximal residue limits in tissues and milk intended for human consumption (Council of the European Communities 1990, Council Regulation 90/2377/EEC) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%